Meningkatkan Hasil Belajar Matematika Menggunakan Alat Peraga Stik Es Krim pada Siswa Kelas II SDI Alexandria - Magdalena, Ina; Nurchayati, Aan; asrifah, Diah Nur (Lembaga Yasin AlSys, 2023)
The purpose of this study was to determine the effectiveness of ice cream stick teaching aids in improving students' learning outcomes in mathematics multiplication material. This research is a classroom action research. The research approach used is a qualitative approach with a class action research type. The source of the data in this study were class 2 students at SDI Alexandria. The method used is the method of observation (observe). In the initial conditions of learning cycle 1 students did not understand what was conveyed by the teacher. At the learning improvement stage in cycle 2, some students almost understood what was conveyed by the teacher. At the stage of improving learning cycle 3 the delivery of objectives and concepts has been understood by students. And the activeness of students and learning outcomes are satisfactory. Student learning also increased, namely some students who got satisfactory grades.